2016
DOI: 10.1900/rds.2016.13.217
|View full text |Cite
|
Sign up to set email alerts
|

Blood Ketones: Measurement, Interpretation, Limitations, and Utility in the Management of Diabetic Ketoacidosis

Abstract: ■ AbstractDiabetic ketoacidosis (DKA) remains a common medical emergency. Over the last few years, new national guidelines have changed the focus in managing the condition from being glucose-centered to ketone-centered. With the advent of advancing technology and the increasing use of hand-held, point-of-care ketone meters, greater emphasis is placed on making treatment decisions based on these readings. Furthermore, recent warnings about euglycemic DKA occurring in people with diabetes using sodium-glucose co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 59 publications
0
84
0
5
Order By: Relevance
“…Glucagon accelerates the generation of ketonemia and hyperglycemia in the insulin deficient state, but as previously mentioned it is not essential for development of diabetic ketoacidosis. In addition to ketone body overproduction, clearance is also decreased in diabetic ketoacidosis 2536…”
Section: Pathophysiologymentioning
confidence: 99%
“…Glucagon accelerates the generation of ketonemia and hyperglycemia in the insulin deficient state, but as previously mentioned it is not essential for development of diabetic ketoacidosis. In addition to ketone body overproduction, clearance is also decreased in diabetic ketoacidosis 2536…”
Section: Pathophysiologymentioning
confidence: 99%
“…Despite the price differential which is often an important consideration, we recommend avoiding urine ketone monitoring and relying only on blood ketone monitoring for the following reasons: Unlike blood ketone monitoring which measures β‐hydroxybutyrate, urine ketone monitoring only measures acetoacetate which is unstable and unreliable for DKA diagnosis (see below) Unlike urine ketone monitoring, blood ketone monitoring has better sensitivity and specificity for DKA; acetoacetate levels rise with the duration of DKA and may be undetectable in urine samples during the early phases of DKA There is poor correlation between urine ketone and plasma ketone levels; notably, ketone estimates from urine samples represent bladder ketone levels since the last void and not current urine ketone levels Resolution of DKA may be missed since treatment‐triggered β‐hydroxybutyrate oxidation would elevate urine acetoacetate levels and present a false‐positive signal indicating persistent DKA …”
Section: Use Of Sglt Inhibitors In Type 1 Diabetes and The Stop Dka Pmentioning
confidence: 99%
“…While the use of lower SGLT inhibitor doses, blood ketone testing and following sick‐day rules have been suggested as ways for patients with T1DM to independently manage their DKA risk, one study involving 2995 patients with T1DM found that more than 30% did not engage in routine ketone testing . Concerns have also been raised about the costs associated with these tests and potentially inaccurate results . Therefore, to determine the risk–benefit ratio and cost‐effectiveness of SGLT inhibitors in T1DM patients, the DKA risk associated with their use requires further investigation, along with examination of other commonly associated side effects such as urinary tract infections (UTIs) …”
Section: Introductionmentioning
confidence: 99%
“…23 Concerns have also been raised about the costs associated with these tests and potentially inaccurate results. 24 Therefore, to determine the riskbenefit ratio and cost-effectiveness of SGLT inhibitors in T1DM patients, the DKA risk associated with their use requires further investigation, along with examination of other commonly associated side effects such as urinary tract infections (UTIs). 25,26 In the absence of head-to-head clinical trials directly comparing SGLT inhibitors and metformin in the T1DM population, their efficacy and safety as adjunctive therapies needs examining indirectly.…”
Section: Introductionmentioning
confidence: 99%